Analisa Manajemen Zakat Untuk Korban Kekerasan Terhadap Perempuan dan Anak; Perspektif Hukum Syariah - Rita Erawati, Raden Rara; Sunaryo Mukhlas, Oyo; Burhanuddin, Burhanuddin; Ishandawi , Ishandawi (Coopetition : Jurnal Ilmiah Manajemen, 2026)
This article examines the potential of zakat as an instrument of protection and empowerment for victims of violence against women and children from a Sharia law perspective. Using a qualitative research approach through an in-depth literature review, this article analyzes the Sharia legal basis for allocating zakat to this vulnerable group. The research findings indicate that victims of violence can be categorized as mustahik (receiver of zakat), specifically those in debt (ghārimīn) and those who strive in the path of Allah (fī sabīlillāh), as long as they meet the criteria established in zakat jurisprudence. This article also identifies various obstacles in distributing zakat to victims of violence, including limited understanding among the community and zakat institutions, and a lack of specific regulations. As a solution, this article proposes an integrative zakat distribution model oriented toward the maqāṣid al-sharīʿah (the means of payment of zakat), which not only provides financial assistance but also supports the holistic recovery of victims. Policy recommendations are proposed to enhance the strategic role of zakat in the social protection system in Indonesia. Keywords: Management of Zakat, Violence against Women and Children, Sharia Law, Maqāṣid al-Sharīʿah, and Empowerment